Oral immunotherapy for peanut allergy: The pro argument - Chinthrajah, R. Sharon; Cao, Shu; Dunham, Theresa; Sampath, Vanitha; Chandra, Sharad; Chen, Meng; Sindher, Sayantani; Nadeau, Kari (The World Allergy Organization journal, 2020)
Food allergy (FA) is a growing public health problem with personal, social, nutritional, and economic consequences. In the United States, it is estimated that 8% of children and 10.8% of adults have food allergies. Allergies to peanuts are particularly worrisome as unlike allergies to other allergenic foods, such as milk and egg, which are commonly outgrown by 5 or 10 years of age, 80% of peanut allergies persist into adulthood. The first drug for peanut allergy, Palforzia, was approved by the US Food and Drug Administration (FDA) in January 2020. For other food allergies, the current standard of care for the management of FA is suboptimal and is limited to dietary elimination of the offending allergen, vigilance against accidental ingestion, and treatment of allergic reactions with antihistamines and epinephrine. However, dietary avoidance can be challenging, and it is estimated that approximately 40% of patients with food allergies report at least one food allergy-related emergency department in their lifetime. Reactions, even from minimal exposures, can be life-threatening. Oral immunotherapy (OIT) has been the best researched therapeutic approach for treating FA over the last decade, with clinical trials investigating its efficacy, safety, and ability to improve participants' quality of life (QoL). A number of studies and meta-analyses have shown that OIT treatment is effective in raising the threshold of reactivity to peanuts and other foods in addition to producing a measurable serum immune response to such therapy. Although OIT-related adverse events (AEs) are common during treatment, serious reactions are rare. In fact, while the majority of patients experience AEs related to dosing, most continue daily dosing in hopes of achieving protection against the culprit food. Moreover, the majority of participants report improvement of QoL after OIT and are positive about undergoing OIT. These results show patients’ commitment to OIT and their optimism regarding the benefits of treatment. As a first step in therapeutic options to protect from reactions to unintentional ingestion of allergenic foods, and importantly, to address the many psychosocial aspects of living with FA, OIT shows promise. Future research will focus on identifying optimal OIT regimens that maintain protection after therapy and allow for regular food consumption without allergic symptoms. Education and informed shared decision making between patients and providers are essential in optimizing current therapy regimens.